Purification and characterization of lipoxygenase from mung bean (Vigna radiata L.) germinating seedlings - Aanangi, Raveendra; Kotapati, Kasi Viswanath; Palaka, Bhagath Kumar; Kedam, Thyagaraju; Kanika, Nirmala Devi; Ampasala, Dinakara Rao (3 Biotech, 2016)
This study reports purification and characterization of lipoxygenase protein from mung bean germinating seedlings. Lipoxygenases (LOXs) are key enzymes in seed germination. The purified mung bean LOX has resolved into two peaks by chromatofocusing, one has highest LOX activity with an isoelectric point of 5.84 and the other has lowest LOX activity with an isoelectric point of 5.52. The purified LOX has molecular mass of approximately 97 kDa and showed high activity with linoleic acid than linolenic acid and arachidonic acid. The optimal activity of LOX was observed at pH 6.5 and temperature 35 °C. Far-UV circular dichroism (CD) studies revealed that the purified mung bean LOX possess secondary structural elements with significant α-helix and β-strands. Further, the secondary structure of mung bean LOX was stable up to 60 °C at pH 6.5. Biophysical and chemical properties of the mung bean LOX are similar to the other legume LOXs and may be considered as type-1 LOX.